FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - ROSVITA ANGGRAENI; MEIRISKA FEBRIANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research is to examine the influence of leverage, size, measure of Public Accounting Firm, profitavility, audit committee and institutional ownership to tax avoidance. The population of this research is all manufacture companies listed in Indonesia Stock Exchange from 2014-2016. Samples areobtained through purposive sampling method, in which only sixty-seven listed manufacture companies in Indonesia Stock Exchange meet the sampling criterias resulting 201 data available are taken as the samples. The research used multiple regression method to test the effect of each variable in influencing tax avoidance. The empirical result indicates that leverage, size and profitability have influence to tax avoidance. However measure of Public Accounting Firm, audit committee and institutional ownership have no influence to tax avoidance.